Nep1-like Proteins from Valsa mali Differentially Regulate Pathogen Virulence and Response to Abiotic Stresses - Jianying Liu; Jiajun Nie; Yali Chang; Lili Huang (Journal of Fungi, 2021)
Necrosis and ethylene-inducing peptide 1(Nep1)-like protein (NLP) is well known for its cytotoxicity and immunogenicity on dicotyledonous, and it has attracted large attention due to its gene expansion and functional diversification in numerous phytopathogens. Here, two NLP family proteins, VmNLP1 and VmNLP2, were identified in the pathogenic fungus Valsa mali. We showed that VmNLP2 but not VmNLP1 induced cell death when transiently expressed in Nicotiana benthamiana. VmNLP2 was also shown to induce cell death in apple leaves via the treatment of the Escherichia coli-produced recombinant protein. VmNLP1 and VmNLP2 transcripts were drastically induced at the early stage of V. mali infection, whereas only VmNLP2 was shown to be essential for pathogen virulence. We also found that VmNLP1 and VmNLP2 are required for maintaining the integrity of cell membranes, and they differentially contribute to V. mali tolerance to salt- and osmo-stresses. Notably, multiple sequence alignment revealed that the second histidine (H) among the conserved heptapeptide (GHRHDWE) of VmNLP2 is mutated to tyrosine (Y). When this tyrosine (Y) was substituted by histidine (H), the variant displayed enhanced cytotoxicity in N. benthamiana, as well as enhanced virulence on apple leaves, suggesting that the virulence role of VmNLP2 probably correlates to its cytotoxicity activity. We further showed that the peptide among VmNLP2, called nlp25 (VmNLP2), triggered strong immune response in Arabidopsis thaliana. This work demonstrates that NLPs from V. mali involve multiple biological roles, and shed new light on how intricately complex the functions of NLP might be.